The Seebeck enhancement of thermoelectric devices in CMOS technology through quantum well confinement - Oxandale, Samuel Warren (Kansas State University, 2023)
Thermoelectric devices convert convert between thermal and electrical energy. The performance of these devices is measured by the thermoelectric figure of merit ZT = (S²σ/κ)T where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the temperature. Improving the thermoelectric figure of merit has proven a significant research challenge due to the interdependence of the properties involved. The Seebeck coefficient and electrical conductivity are both tied to the curvature of electron bands, and increasing one almost always results in a decrease in the other. While thermal conductivity can be decreased through phonon scattering, scattering mechanisms also scatter electrons, decreasing the electrical conductivity, counteracting any gains. Aside from material engineering, pushing beyond the current limits on the thermoelectric figure of merit will depend on our ability to decouple the Seebeck coefficient, electrical conductivity, and thermal conductivity. This dissertation details such a path, where we enhance thermoelectric materials using quantum confinement to decouple the three properties. While quantum confinement has historically been achieved through physically small devices, such as two-dimensional superlattices, nanowires, and quantum dots, here we achieve it through electrical isolation using two-dimensional electron and hole gases in metal-oxide-semiconductor field effect transistors (MOSFETs). Under strong inversion, the two-dimensional gases form in the channel of the MOSFETs, separating the electrical path from the thermal path. Furthermore, the channel depth is constrained to quantum sizes, enabling the non-zero saturation of the Seebeck coefficient as electrical conductivity is increased. The result is a non-classical, linearly increasing power factor S²σ that is decoupled from thermal conductivity. This work compares the MOSFET thermoelectric devices to similar silicon devices doped to the same concentration as the MOSFET channel in order to isolate the quantum confinement effects in the two-dimensional gases formed in the MOSFET channel under strong inversion. The electrical conductivity, thermal conductivity, and Seebeck coefficient of the devices were measured and compared. In the p-type MOSFETS, we observe a 12-factor increase in performance over bulk silicon devices. The n-type MOSFETs showed a similar 8-factor increase in performance. This work is the first demonstration of the quantum enhancement of the Seebeck coefficent and power factor using an electrically defined quantum channel, laying the foundation for microelectronic-based, chip-scale thermoelectric cooling and energy-scavenging applications.
Keywords: Thermoelectrics; Solid state physics; Quantum systems; Semiconductor devices; MOSFETs